2004
DOI: 10.4067/s0716-078x2004000400005
|View full text |Cite
|
Sign up to set email alerts
|

Activity budget patterns in family-group and solitary territorial male guanacos

Abstract: We observed behavioral patterns of territorial male guanacos (Lama guanicoe) in Torres del Paine National Park, Chile. Both solo territorial males and family-group territorial males were observed to compare the activity time budgets of males (n = 23) in different social groups and habitats. We found no difference in the activity time budgets of males based on social group type, total number of females or all guanacos present, or age of territorial males. Males, in all categories, spent most of their time forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In applications where one needs to know sex and age structure, this problem can be minimized, if not overcome, if surveys are conducted towards the end of the birth season when chulengos are abundant. In addition, with training and experience, sexes can be identified even at moderate distance by morphological characteristics (testes/vulva, penis/mammary gland, and body shape) and behavioral cues, as demonstrated by field studies with a more acceptable 3 to 5% unclassified animals Fritz 1991, Fritz andFranklin 1994;Ortega and Franklin 1995;Sarno and Franklin 1999;Young and Franklin 2004b). Methodological improvements by guanaco researchers and managers need to be made to substantially increase the reliability of field identification of guanaco sexes and social groups.…”
Section: Discussionmentioning
confidence: 99%
“…In applications where one needs to know sex and age structure, this problem can be minimized, if not overcome, if surveys are conducted towards the end of the birth season when chulengos are abundant. In addition, with training and experience, sexes can be identified even at moderate distance by morphological characteristics (testes/vulva, penis/mammary gland, and body shape) and behavioral cues, as demonstrated by field studies with a more acceptable 3 to 5% unclassified animals Fritz 1991, Fritz andFranklin 1994;Ortega and Franklin 1995;Sarno and Franklin 1999;Young and Franklin 2004b). Methodological improvements by guanaco researchers and managers need to be made to substantially increase the reliability of field identification of guanaco sexes and social groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, a group of females with their offspring of the year live within a territory that an adult male defends (Raedeke 1979;Franklin 1983;Bank et al 2003;Young and Franklin 2004a, b). Territorial males engage in a series of time-and energy-consuming activities, such as being vigilant to detect potential intruders, patrolling borders, and reinforcing territory ownership through defecating-urinating displays directed towards neighbors and peripheral males (Franklin 1983;Young and Franklin 2004a). Eventually, outsiders cross territory boundaries, ultimately triggering chases and direct fights.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, territorial defense implies time-consuming activities that are undertaken at the expense of other mutually exclusive and potentially beneficial ones, such as feeding. The territorial defense effort has been assessed in family-group and solitary territorial male guanacos (Young and Franklin 2004a), but systematic comparisons between territorial males and males who are not engaged in reproductive activities are lacking. In contrast to territorial males, bachelors are mostly mature males who do not hold a territory and live within large male groups in which individuals enter and leave freely (Raedeke 1979;Franklin 1983).…”
Section: Introductionmentioning
confidence: 99%
“…those that survived the critical post-release period (Armstrong and Seddon 2008), invested more time in vigilance and less time in foraging than those previously reported (Marino and Baldi 2008), which may suggest some degree of stress that might have had a negative influence on the welfare of individuals. On the other hand, during the time of the present study, individuals exhibited the expected behavioural patterns indicated for the species (Raedeke 1979;Young and Franklin 2004;González et al 2006;Marino and Baldi 2008), in which foraging and vigilance time allocation are influenced by both guanaco social organization and ecological variables. Further studies will be necessary, however, when the guanaco population becomes larger and the reproductive group increases, to determine other factors that may influence vigilance and foraging behaviour, such as group-size effect, predation level or potential environmental stressors in the area of the QCNP.…”
Section: Discussionmentioning
confidence: 86%
“…According to the criteria by Young and Franklin (2004) and Marino and Baldi (2008), behaviours were defined as "vigilant", when the individual was standing with the head in an upright position, scanning the surrounding areas, and "foraging", when the individual was standing or walking slowly, handling food, with the head below the shoulder level.…”
Section: Behavioural Observationsmentioning
confidence: 99%